1995
DOI: 10.1523/jneurosci.15-11-07653.1995
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral role for nitric oxide in chemosensory activation of feeding in a mollusc

Abstract: A role for the NO-cGMP pathway in mediating chemosensory activation of feeding is suggested by intense NADPH diaphorase staining observed in nerve fibers that project from sensory cells in the lips to the CNS and by the presence in the CNS of a NO-activated guanylyl cyclase. In preparations reduced to isolated lips and CNS, intracellular recordings were made from motoneurons driven by the interneurons of the central pattern generator (CPG) for feeding. Fictive feeding in such preparations can be recorded from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
129
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 33 publications
11
129
3
Order By: Relevance
“…Despite the diffuse nature of its delivery, it is clear that NO activates and modulates particular neural network targets with stereotypical functional consequences (Moroz et al, 1993;Gelperin, 1994;Elphick et al, 1995;Scholz et al, 2001). This suggests that particular distributions of NO receptors (and/or other downstream targets) may enable a diffuse NO signal to sculpt the responses of specific cells within a population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the diffuse nature of its delivery, it is clear that NO activates and modulates particular neural network targets with stereotypical functional consequences (Moroz et al, 1993;Gelperin, 1994;Elphick et al, 1995;Scholz et al, 2001). This suggests that particular distributions of NO receptors (and/or other downstream targets) may enable a diffuse NO signal to sculpt the responses of specific cells within a population.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its rapid membrane-permeating characteristics and short half-life in biological tissues, NO is typically used to transmit information between closely juxtaposed cells. For example, NO serves as a local modulator of blood pressure (Shesely et al, 1996;Hanafy et al, 2001), cardiac function (Balligand et al, 1993;Keaney et al, 1996;Zahradnikova et al, 1997;Gyurko et al, 2000), neuronal development (Cramer et al, 1998;Scholz et al, 1998;Champlin and Truman, 2000), synaptic transmission (Schuman and Madison, 1994;Huang, 1997), and oscillatory behavior in patterngenerating networks of neurons (Pape and Mager, 1992;Moroz et al, 1993;Gelperin, 1994;Elphick et al, 1995;Hedrick and Morales, 1999;Scholz et al, 2001;Newcomb and Watson, 2002;McLean and Sillar, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Bakken et al (2012) showed that the ratio of N2O/(N2+N2O) is negatively 555 correlated with soil pH over the pH range 5-8, which is typical for 556 agricultural soils. The authors concluded that low pH interfers with the 557 synthesis of the N2O reductase enzyme, most likely by affecting the enzyme 558 assembly in the periplasm.…”
Section: Paracoccus 356mentioning
confidence: 99%
“…It also suggests that electrophysiological identification of specific NO-sensitive neurons is likely to be quite straightforward. Although our understanding of the function of the NO/cyclic GMP pathway in invertebrate nervous systems is in its infancy, several potential roles have been established, including modulation of synaptic efficacy (Pivovarov et al, 1990(Pivovarov et al, , 1995Mothet et al, 1996), sensory integration (Gelperin, 1994;Muller and Hildebrandt, 1995;Elphick et al, 1996), central pattern generation (Moroz et al, 1993;Elphick et al, 1995), higher information processing (Muller, 1996), and control over neural development (Scholz et al, 1995;Kuzin et al, 1996;Truman et al, 1996). The large sizes and reproducible locations of the NO-sensitive cells in the lobster nervous system offer the prospect of further evaluating the properties of this important second messenger pathway in a relatively simple and well-studied set of neuronal networks.…”
Section: Discussionmentioning
confidence: 99%